Όταν τα πεύκα είχαν πρόσωπο: Οι ρετσινάδες του Αμπελικού Λέσβου - Curep (Πανεπιστήμιο Αιγαίου, 2015)
Εμφανίστηκαν οι Αντώνης Βερβέρης, Νίκος Βερβέρης, Παναγιώτης Βερβέρης, Νίκος Καρλαγάνης, Μαρία Μελιγονίτη, Στάθης Μελιγονίτης, Κώστας Σιταράς, Νίκος Σωτήρχος, Μαρία Χατζηγιάννη, Στρατής Χονδρής